Tracing the Spectrum of Inborn Errors of Immunity from Past to Present - BARIŞ, SAFA (My University, 2024)
Human inborn errors of immunity (IEI) constitute a constellation of genetic disorders with profound implications for immune system function, leading to recurrent infections, immune dysregulations, and malignancies. The field of IEI has undergone a tremendous evolution over the course of seventy years, with substantial strides in comprehending the clinical and immunological aspects of monogenic disorders. Furthermore, these endeavors have synergized with innovative therapeutic modalities, forging a trajectory toward enhanced patient care. These advances promise to favorably transform the outcomes of many IEI to provide patients with increased life expectancy and improved quality of life. In this special issue of the Turkish Journal of Immunology, we will survey some recent advances in the field of IEI with a focus on disease pathogenesis and outcomes.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; İmmünoloji ve Alerji; Immunology and Allergy; Immunology; diagnosis; Inborn errors of immunity; outcome; primary immune deficiencies; treatment